Дороги: книга стихов : перевод с удмуртского / Флор Васильев - Васильев Флор Иванович (Советская Россия, 1981)
Экземпляры: Ч/з (20221011) / Инвентарный номер: 118667 / Цена: 10.00 / Авт.знак: В 19 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)